2021
DOI: 10.1093/eurjpc/zwab229
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of lomitapide in homozygous familial hypercholesterolaemia: the pan-European retrospective observational study

Abstract: Background Lomitapide is a lipid-lowering agent indicated as adjunct therapy for adult HoFH Objectives This study evaluated the medium-term effectiveness and safety of lomitapide in a large cohort of HoFH patients in Europe. Methods In a multicenter retrospective, observational study including 75 HoFH patients treated with lomitapide in a real-world clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
2
27
2
Order By: Relevance
“…This is a post hoc analysis of the Pan-European Lomitapide Study ( D’Erasmo et al, 2021b ) performed on a subgroup of patients diagnosed with ARH due to homozygous mutation in LDLRAP1 . The Pan-European Lomitapide Study was a multicenter, observational, and retrospective survey collecting data from all patients known to be receiving lomitapide in Europe in the context of usual clinical practice and without protocol-mandated procedures ( D’Erasmo et al, 2021b ). The protocol of the Pan-European Lomitapide Study has been reported in detail elsewhere ( D’Erasmo et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a post hoc analysis of the Pan-European Lomitapide Study ( D’Erasmo et al, 2021b ) performed on a subgroup of patients diagnosed with ARH due to homozygous mutation in LDLRAP1 . The Pan-European Lomitapide Study was a multicenter, observational, and retrospective survey collecting data from all patients known to be receiving lomitapide in Europe in the context of usual clinical practice and without protocol-mandated procedures ( D’Erasmo et al, 2021b ). The protocol of the Pan-European Lomitapide Study has been reported in detail elsewhere ( D’Erasmo et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…The Pan-European Lomitapide Study was a multicenter, observational, and retrospective survey collecting data from all patients known to be receiving lomitapide in Europe in the context of usual clinical practice and without protocol-mandated procedures ( D’Erasmo et al, 2021b ). The protocol of the Pan-European Lomitapide Study has been reported in detail elsewhere ( D’Erasmo et al, 2021b ). For a brief period, physicians were asked to retrospectively retrieve demographic and clinical information from medical records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a real-world European study, lomitapide has been proved to be a very effective adjuvant drug to reduce LDL-C in HoFH patients for the longest follow-up period so far. 279 As lomitapide blocks MTP, it leads to impaired intestinal fat transport, making gastrointestinal symptoms as the most common adverse event in patients. 280 In terms of safety, lomitapide-related hepatic steatosis may not indirectly increase the risk of liver fibrosis, and the data suggest that lomitapide may reduce cardiovascular events in HoFH patients.…”
Section: Cholesterol-related Diseases and Interventionsmentioning
confidence: 99%
“… 280 In terms of safety, lomitapide-related hepatic steatosis may not indirectly increase the risk of liver fibrosis, and the data suggest that lomitapide may reduce cardiovascular events in HoFH patients. 279 …”
Section: Cholesterol-related Diseases and Interventionsmentioning
confidence: 99%